Cerebellar Infarction Complicated with Acute Hydrocephalus: A Case Report - Demir, Caner F.; Ozdemir, Hasan H.; Tasci, Irem; Kaplan, Metin; Karaboga, Fatih (Turkish Neurological Soc, 2012)
Acute hydrocephalus is a rare manifestation of posterior circulation strokes. We present a patient with cerebellar infarct and secondary obstructive hydrocephalus. The patient's brain computed tomography scan showed severe third and lateral ventricular dilation suggestive of obstructive hydrocephalus. Following shunt placement, the patient recovered and was able to walk without assistance.
Akut hidrosefali komplikasyonlu serebellar enfarkt: Olgu sunumu
Keywords: Cerebellar infarction; acute hydrocephalus